2021
DOI: 10.1021/acs.iecr.0c05392
|View full text |Cite
|
Sign up to set email alerts
|

Role of Carbon Capture, Storage, and Utilization to Enable a Net-Zero-CO2-Emissions Aviation Sector

Abstract: A techno-economic analysis of viable scenarios for the aviation industry to achieve net-zero CO 2 emissions is presented. These scenarios are based (i) on carbon capture and storage (CCS), where conventional fossil jet fuel is produced, and the corresponding emissions are offset by capturing CO 2 , either via direct air capture (DAC-CCS route) or via point-source capture (PSC-CCS route), and permanently storing it underground, and (ii) on carbon capture and utilization (CCU), where synthetic jet fuel is produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(71 citation statements)
references
References 46 publications
1
64
0
Order By: Relevance
“…In fact, we found this result somewhat surprising given the energy density of fossil fuels and the efficiencies of modern refineries. Our results mirror those of previous work, ,, which found that e-fuels required significantly higher energy intensity than biofuels due to their hydrogen consumption to remove the oxygen from CO 2 . They also concluded that carbon capture and storage rather than utilization provided a route to decarbonize aviation fuels at lower cost and energy, despite differences in their assumptions on DAC and fuel production relative to ours.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In fact, we found this result somewhat surprising given the energy density of fossil fuels and the efficiencies of modern refineries. Our results mirror those of previous work, ,, which found that e-fuels required significantly higher energy intensity than biofuels due to their hydrogen consumption to remove the oxygen from CO 2 . They also concluded that carbon capture and storage rather than utilization provided a route to decarbonize aviation fuels at lower cost and energy, despite differences in their assumptions on DAC and fuel production relative to ours.…”
Section: Discussionsupporting
confidence: 90%
“…This thought experiment follows in the footsteps of other systems analyses that have examined questions associated with enabling a net zero chemical industry, , aviation fuels, and more broadly hydrocarbon fuels . These studies abstract the key elements of processes for chemicals and fuels to provide higher level insights into the trade-offs between using biomass as a feedstock, carbon capture, and CO 2 storage versus utilization. , Moreover, technoeconomic, carbon footprint, and land use metrics have also been examined .…”
Section: Defining the Thought Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Humankind faces an urgent challenge to rapidly reduce greenhouse gas emissions in order to reach a carbon neutral society by 2050, the point at which environmental changes caused by climate change may become irreversible. , Among the many technologies being developed toward this goal, it has been argued that carbon dioxide capture, utilization, and storage (CCUS) is a necessary component, being both a mature and relatively inexpensive measure that can support other initiatives in electrochemical storage, renewable energy conversion, and improving industrial efficiency. Not only is CCUS an environmental necessity, but it also represents a significant economic opportunity. , Recent governmental and industrial white papers highlight its vital role in “power to X” (P2X) schemes that seek to harness electricity to synthesize various energy-dense fuel sources by utilizing H 2 from electrolysis combined with CO 2 from capture. P2X represents just one of several proposed industrial processes aiming to use CO 2 as a feedstock, underlining the need for efficient CCUS implementation.…”
Section: Introduction and Objectives: Co2 Capture By Metal Oxidesmentioning
confidence: 99%
“…Therefore, CO 2 capture, and utilization (CCU) might be more of a distraction rather than a viable option to mitigate climate change (Mac Dowell et al, 2017). This holds especially true for energy intensive CCU processes, e.g., the production of synthetic fuels, which require large amounts of carbon-free electricity (Abanades et al, 2017;Sutter et al, 2019;Becattini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%